A Coarse-Grained Molecular Dynamics Simulation Using NAMD Package to Reveal Aggregation Profile of Phospholipids Self-Assembly in Water - Dwi Hudiyanti; Muhammad Radifar; Tri Joko Raharjo; Narsito Narsito; Sri Noegrohati (Journal of Chemistry)
The energy profile of self-assembly process of DLPE, DLPS, DOPE, DOPS, DLiPE, and DLiPS in water was investigated by a coarse-grained molecular dynamics simulation using NAMD package. The self-assembly process was initiated from random configurations. The simulation was carried out for 160 ns. This study presented proof that there were three major self-assembled arrangements which became visible for a certain duration when the simulation took place, that is, liposome, deformed liposome, and planar bilayer. The energy profile that shows plateau at the time of these structures emerge confirmed their stability therein. Our findings have highlighted the idea that liposomes and deformed liposomes are metastable phases which eventually will turn into planar bilayer, the stable one.